Establishing Cognitive Strategies to Support Online English Language Learners’ Critical Thinking - Prasetya, Rizky (Universitas PGRI Adi Buana Surabaya, 2022)
Shifting to online-based teaching and learning has become the most obvious way to increase pedagogy sustainability in nations with the current implementation of an online learning environment. Research has shown that online learning and teaching in English language subjects influence the cognitive strategy environment. This research aims to determine and explore the cognitive strategy implemented in the online learning environment to support the critical thinking of English language learners. This study is a quantitative descriptive study accomplished online utilising survey methodologies. The sample selection method is simple random sampling. Primary data was collected in this study by distributing questionnaires to 115 respondents via the internet. Data was gathered via the completion of questions provided to all respondents in the survey. In addition, the data were evaluated in order to be characterised and described. The data analysis findings of English language lecturers’ surveys indicate that the cognitive strategy used during the online teaching situation was prosperous and profligate. The cognitive strategies necessitated implementing the online English language learners’ critical thinking included procedural, metacognitive, conceptual, and strategic. This research establishes that the cognitive strategy implementation of online learning is commonly advantageous during remote teaching. The survey indicated that just 73% of English lecturers considered cognitive strategy online platforms as beneficial as traditional meetings for supporting critical thinking. Positive responses were obtained from the questionnaire. In addition, the statement is relevant to their experience and background in online teaching, which indicates a good attitude toward the cognitive strategy that works well in their online learning mechanism. The research suggests that online pedagogy and English lecturers’ must be developed to pave the way for a potential future authentic online strategy. The research may illustrate the difficulties associated with online education and potential areas for improvement..